Impelementasi Pendekatan Pembelajaran Problem Posingdan Pengaruhnya Terhadap Hasil Belajar Matematika - Kadir Kadir (Jurnal Pendidikan dan Kebudayaan, 2011)
The objective of the present study is to find out the effect of implementation of problem posing approach on the students’learning outcome in mathematics. The study was conducted in MTsN 22 Kampus B Munjul Jakarta Timur at academic year 2005/2006. There were 7th grade students as the sample of the study, selected through cluster random sampling. The data were gathered by using a test. Data analysis was done by using t -test. The results of the study have revealed that problem posing approach effected the students’ learning outcome in mathematics. Learning in mathematics by problem posing approach can make the students be active and creative, it was shown at competences of the students to develop math’s problem themselves, manage, and to explore the information for posing the mathematics’ problem that is solvable. Through instructional by problem posing approach can also improve the students’ activity in teaching and learning, especially interacting and sharing ideas on both the students each other and the teacher, so learning activity is becoming meaningful the students’ mastery of the concept. ABSTRAKTujuan penelitian ini dimaksudkan untuk mempelajari pengaruh pembelajaran dengan pendekatan problem posingterhadap hasil belajar matematika. Penelitian dilakukan di MTs Negeri 22 Kampus B Munjul Jakarta Timur Tahun Pelajaran 2005/2006 dengan menggunakan metode eksperimen. Sampel penelitian sebanyak 90 siswa kelas VII yang dipilih dengan teknik cluster random sampling. Data dikumpulkan dengan menggunakan tes, selanjutnya dianalisis dengan menggunakan statistik uji-t. Hasil penelitian mengungkapkan pendekatan problem posingberpengaruh nyata terhadap hasil belajar matematika. Pembelajaran matematika dengan pendekatan problem posing mampu membuat siswa aktif dan kreatif, terlihat dari kemampuan siswa mengembangkan masalah matematika sendiri, mengolah dan mengeksplorasi informasi yang ada dan mengajukan masalah matematika yang dapat diselesaikan. Melalui pembelajaran dengan pendekatan problem posing juga dapat meningkatkan aktivitas siswa dalam proses pembelajaran, khususnya dalam berinteraksi dan sharing ideadiantara siswa dan guru sehingga kegiatan pembelajaran lebih bermakna dan pemahaman siswa terhadap konsep menjadi lebih baik.